Fractional CO2 laser treatment effect on cervicovaginal lavage zinc and copper levels: a prospective cohort study - Attila G. Sipos; Krisztina Pákozdy; Szilvia Jäger; Kindra Larson; Peter Takacs; Bence Kozma (BMC, 2021)
Abstract Background The basic principle of vaginal laser therapy is the rejuvenation of the affected tissue. Zinc and copper are essential nutritional trace elements and have a key role in connective tissue homeostasis. We aimed to investigate the effect of vaginal, fractional CO2 laser treatment on cervicovaginal lavage (CVL) zinc and copper levels. Methods Twenty-nine postmenopausal women with symptoms of vaginal dryness were enrolled in our prospective cohort study. Three treatments with MonaLisa Touch CO2 laser system were performed four weeks apart. At each treatment CVL was collected, Vaginal Health Index (VHI) was obtained, and Visual Analog Scale (VAS) for vaginal dryness was assigned by patients. Zinc and copper concentrations were measured with optical emission spectrometry before each treatment and six weeks after the 3rd treatment. Results The VHI scores significantly improved after each laser treatment (mean ± SD VHI score, 13.03 ± 4.49 before vs. 15.55 ± 4.35 after the 1st, 17.79 ± 4.57 after the 2nd and 19.38 ± 4.39 after the 3rd treatment, P < 0.01). Similarly, VAS scores reflected improvement (mean ± SD VAS score 6.59 ± 2.86 before vs. 4.17 ± 2.86 after the 1st, 2.45 ± 2.43 after the 2nd and 1.41 ± 1.94 after the 3rd treatment, P < 0.01). CVL zinc levels were significantly higher compared to copper levels (0.06 ± 0.04 vs. 0.006 ± 0.006 mg/L, P < 0.01) at baseline. While copper levels remained the same through treatments, the CVL zinc level was significantly higher after the second laser treatment compared to the baseline. Conclusions Fractional CO2 laser treatment of the vagina impacts CVL zinc and copper levels differently. While CVL copper levels were not different after each laser treatment, zinc levels were significantly higher after the second treatment before returning to baseline values.